2022
DOI: 10.1021/acs.jafc.2c02729
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Ameliorates Nonalcoholic Steatohepatitis through Thyroid Hormone-Responsive Protein Signaling and the Gut Microbiota-Mediated Metabolism of Bile Acids

Abstract: Spermidine, a natural polyamine and physiological autophagy inducer, is involved in various physiological processes. However, the impact and mechanism of spermidine on nonalcoholic steatohepatitis (NASH) remains unclarified. We found that daily spermidine intake was significantly lower in volunteers with liver dysfunction than the healthy controls, and the serum and fecal spermidine levels were negatively correlated with the NASH phenotypes. Spermidine supplementation significantly attenuated hepatic lipid acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Studies exploring oral supplementation of spermidine are scarce. Ni et al reported that oral administration of spermidine did not reduce body weights of Western diet-fed animals, but, in contrast, improved serum triglyceride (TG) levels, hepatic steatosis, glucose tolerance and insulin resistance [ 26 ]. In our study, serum TG levels were decreased by spermidine in the HSD-S group in week 29 as well as in the HFD-S group in week 10 ( Figure 4 O,P), pointing to diet- and time-dependent spermidine effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies exploring oral supplementation of spermidine are scarce. Ni et al reported that oral administration of spermidine did not reduce body weights of Western diet-fed animals, but, in contrast, improved serum triglyceride (TG) levels, hepatic steatosis, glucose tolerance and insulin resistance [ 26 ]. In our study, serum TG levels were decreased by spermidine in the HSD-S group in week 29 as well as in the HFD-S group in week 10 ( Figure 4 O,P), pointing to diet- and time-dependent spermidine effects.…”
Section: Discussionmentioning
confidence: 99%
“…One obvious difference between the study of Ni et al and our study is the different diet systems. While we used either an HFD (35% fat, mainly cholesterol-rich lard) or an HSD (46% sucrose), Ni et al used a Western diet composed of 40% fat, 41% sucrose and 1.25% cholesterol and additionally used fructose/glucose-enriched drinking water [ 26 ]. Therefore, the diet-related metabolic profiles of the mice were likely different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, akebia saponin D (ASD), extracts from Akebia quinata [ 102 ], and capsaicin, an extract of Capsicum annuum [ 103 ], a common dietary supplement, have been shown to exert beneficial effects on NAFLD via autophagy induction. Spermidine, a natural polyamine and health supplement, is a potent autophagy stimulator and counters lipid-induced liver damage via autophagy enhancement [ 104 ]. ω-3 fatty acids present in fish oil, flaxseeds, and walnuts prevent FFA-induced lipotoxicity through induction of autophagy in NAFLD [ 105 ].…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%
“…However, clinical data failed to confirm any positive effects of spermidine on age-related cognitive decline in contrast to preclinical studies, implying a respective effect [28]. The same also applies to the putative role of spermidine in other age-related diseases [8,29], cardiovascular health [30][31][32], nonalcoholic steatohepatitis (NASH) [33], Alzheimer's disease [34], immune functions [35], and ophthalmology [36].…”
Section: Introductionmentioning
confidence: 99%